Metodología de procedimientos de seguridad para el control de riesgos eléctricos en instalaciones de baja y media tensión en la EERSSA. - Silva Medina, Segundo Manuel (2014)
Power supply system includes the set of useful elements for the generation, transport and distribution of electrical energy. This set is equipped with mechanisms of control, safety and protection. According to the levels of voltage electrification systems are classified into: • Very low voltage (MBT): corresponds to up to 50 tensions and in DC or equal values efficient between phases in alternate current. • Low voltage (LV): corresponds to voltages above 50 V and up to 1,000 V in equal effective values between phases AC or DC. • Medium voltage (MT): corresponds to voltages above 1000 V and up to 33. 000V, inclusive; • High voltage (AT): corresponds to voltages above 33. 000V.Any equipment or part of the electronic system must have all exposed metal grounded. Systems in which any exposed metal part of the circuit should be an exception and should follow the recommendations of safety distance from the next section. Operations and maneuvers to leave tension-free installation, before "work without tension", and the replacement of the voltage, at the end, made them authorized workers who, in the case of high-voltage installations, must be skilled workers. And keep in mind the "5 golden rules", reference a: Visible Court, locking and interlocking, absence of voltage, Earth and short-circuit; and finally the signal. The work in voltage may be performed by skilled workers, following a procedure previously studied and established by the company in charge of the work; taking into account the complexity, tested without tension and that everything conforms to the requirements and safety standards. Works in places where communication is difficult, its orography, confinement or other circumstances, should be done being present, at least two workers with training in first aid.